Ground creeper to smother weeds - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Farmers in West Africa are using the leguminous ground creeper Mucuna utilis, to smother and kill serious grass weeds. Researchers at the International Institute of Tropical Agriculture (IITA) in Nigeria have been working with Mucuna for several...